Hypoxic Changes in Conducting Tissue of the Heart in Sudden Death in Infancy Syndrome - Ferris, James A. J. (1973)
In a group of 50 sudden unexpected infant deaths serial sectioning of the hearts has revealed in 11 cases the presence of petechial haemorrhages in the region of the sinus node and internodal conducting tissue tracts. It is suggested that these findings indicate myocardial hypoxia and that such disturbance of the conducting system may well account for a failure to survive in the sudden death in infancy syndrome.